Alkali-Activated Cement Subject to Alkali-Aggregate Reaction - de Moraes, M. C; Buth, I. S; da Luz, C. Angulski; Langaro, E. A; Medeiros, M. H. F (ACI materials journal, 2021)
Recently, alkali-activated cement (AAC) has been studied to partially replace portland cement (PC) to reduce the environmental impact caused by civil construction and the cement industry. However, with regard to durability, few studies have addressed the behavior of AAC. This study aimed to evaluate the performance of AAC made from blast-furnace slag with contents of 4 and 5% sodium hydroxide as an activator ([Na.sub.2][O.sub.eq] of 3.72% and 4.42%, respectively) when subjected to alkali-aggregate reaction (AAR). Length variation tests were carried out on mortar bars immersed in NaOH solution (1 N of NaOH, T = 80[degrees]C [176[degrees]F]) and on concrete bars (T = 60[degrees]C [140[degrees]F], RH = 95%); compressive strengths tests and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) analyses were also made. Two types of PC were used as a comparison. The results showed good behavior of the AAC in relation to the AAR, with expansions lower than those established by the norm (34% of the limit) and without the finding of losses of mechanical resistance or structural integrity. The alkaline activator content had a small influence on the behavior of the AACs, in which the lowest amount of NaOH (4%) showed fewer expansions (only 15% of the limit established by the norm). Even for the highest activator content (5%), the results were good and comparable to those of PC with pozzolans, which is recommended for the inhibition of AAR. Keywords: alkali-activated cement; alkali-aggregate reaction; blastfurnace slag from charcoal.